Genetic Regulation of Fruit Shape in Horticultural Crops: A Review - Jia Liu; Yang Xu; Pingping Fang; Qinwei Guo; Wenjuan Huang; Jiexi Hou; Hongjian Wan; Sheng Zhang (Horticulturae)
The shape of fruits is a critical trait affecting the commercial value and consumer acceptance of horticultural crops. Genetic regulation of fruit shape involves complex interactions among multiple genes and environmental factors. This review summarizes recent advances in understanding the genetic mechanisms controlling fruit shape in several key horticultural crops, including tomato, pepper, cucumber, peach, and grape. We present the identification and characterization of genes and quantitative trait loci (QTLs) that influence fruit shape, focusing on the roles of genes such as OVATE, SUN, FAS, LC, ENO, GLOBE, CsSUN, CsFUL1, CsCRC, PpCAD1, PpOFP1, and VvSUN. This review highlights the importance of hormonal pathways, particularly those involving synthesis and concentration of cytokinins and brassinosteroids in shaping fruit morphology, and explores how these genes interact and form regulatory networks that collectively determine the final fruit shape. This knowledge provides a foundation for developing strategies to improve fruit quality and yield through genetic modification and breeding programs.